Analisis Yuridis Peraturan Menteri Dalam Negeri Republik Indonesia Nomor 2 Tahun 2016 Tentang Kartu Identitas Anak - Sari, Gita Madiya (Lex Librum : Jurnal Ilmu Hukum, 2024)
The problem of population has become a major problem for the world as a whole because it covers many aspects. One of the countries with the largest population is Indonesia. Occupation administrative arrangements must be made to enhance the establishment, protection, and public service to protect and fulfil the constitutional rights of citizens. These arrangements should also be made for the protection and recognition of all occupancy events and important events experienced by the inhabitants of Indonesia and Indonesian citizens who are outside the territory of the United States of the Republic of Indonesia. The method of normative jurisprudence is a normative juridical approach as research is carried out against the laws and regulations of the government as well as literature. Ministry of Home Affairs Regulation No. 2 of 2016 on the Child Identity Card, which obliges the public to comply with it, is ineffective in its implementation because it is incompatible with its useful functions with the previously existing system of occupation administration, namely the Birth Certificate.